Design of Medical Devices with Usability in Mind: A Theoretical Proposal and Experimental Case Study Using the LEPRE Device - Raffaele Formicola; Cinzia Amici; Maurizio Mor; Luciano Bissolotti; Alberto Borboni (Designs, 2023)
Usability is a critical product feature and is required for widespread market adoption. Standards on usability are highly focused on evaluation procedures and specific aspects, such as software issues or human–machine interaction, whereas the relative scientific literature is very normative oriented. The few methodological works dealing with usability either consider it as one of the many attributes that a particular project must satisfy or present very general methods. No design methods systematically oriented toward the integration of usability and usability-related constraints have been developed to date. This paper presents a usability-oriented model for the design of medical devices and its application to the design of LEPRE, a medical device for upper- and lower-limb robotic rehabilitation. Two methods were used to assess the device’s usability: interviews with experts to outline qualitative evaluations and System Usability Scale (SUS) questionnaires on eight physiotherapists, two physiatrists, and 12 patients, enabling a quantitative assessment. Results support the intention of providing an integrated methodological approach to be applied from the early stages of the project, thus saving time and costs, leading to a more linear product development for this application.